Physical activity patterns of kindergarten children in comparison to teenagers and young adults - Sigmund, Erik; De Ste Croix, Mark; Miklánková, Ludmila; Frömel, Karel (European journal of public health, 2007)
BACKGROUND: Due to the increasing occurrence of obesity and low physical activity (PA) reported in school children there is a need to investigate PA patterns of preschool children. Our aim was to identify the PA of preschool children in comparison to the PA of teenagers and young adults. METHODS: PA of 104 Czech preschool children (aged 5-7 years), 1174 teenagers (aged 12-17 years) and 787 young adults (aged 18-24 years) was determined using Caltrac accelerometery. PA was evaluated on the basis of activity energy expenditure (AEE--kcal kg(-1) day(-1)). Subjects were monitored over 7 days to include a weekend. RESULTS: The AEE in preschool children was significantly higher in comparison to all age groups of teenagers and young adults during both weekdays and at the weekend (P<0.0001). On weekdays during leisure time, preschoolers were considerably more physically active than all categories of teenagers and young adults (P<0.001). Preschoolers show similarities in PA level between weekdays and weekends, unlike the older age groups. CONCLUSION: It seems to appear that organized daily PA (2x20 min of exercising on carpet, 50-70 min of walking outdoors) in preschool children along with enough space for spontaneous PA establishes prerequisites for their further healthy development.
Keywords: Obesity; volnočasové aktivity; cvičení; mladiství; Czechoslovakia; Československo; mužské pohlaví; Adult; Monitoring, Ambulatory; dítě; Child; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; obezita; Exercise; dospělí; Female; ambulantní monitorování; Leisure Activities; Adolescent; lidé; Male